2009
DOI: 10.1038/jhg.2009.83
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ACE and ApoE polymorphisms on myocardial perfusion: correlation with myocardial single photon emission computed tomographic imaging

Abstract: Coronary artery disease is associated with multiple genetic and environmental risk factors. In this study, we evaluated the correlation of angiotensin l-converting enzyme (ACE) (I/D) and ApoE gene polymorphisms (E2, E3, E4 and g.-219G/T) with myocardial perfusion. We examined 410 patients using exercise-rest myocardial perfusion single photon emission computed tomography (SPECT), in which the summed stress score (SSS), summed rest score (SRS) and summed difference score (SDS) indexes were calculated. Homozygot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…There are very few large studies examining the role of apoe4 in relation to coronary atherosclerosis. One study of patients aged 61 years (mean) who underwent exercise-rest myocardial perfusion single positron emission computed tomography (SPECT) reported that individuals who were homozygous for e3 and e4 and individuals who were heterozygous for e4 had significantly higher values of a summed stress score (SSS) compared with those who were heterozygous for the e3 allele ( P  < 0.001) [22]. After adjustment for demographic and clinical risk factors, both APOE genotypes were independent predictors, with a cumulative contribution for the prediction of SSS and summed difference score.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…There are very few large studies examining the role of apoe4 in relation to coronary atherosclerosis. One study of patients aged 61 years (mean) who underwent exercise-rest myocardial perfusion single positron emission computed tomography (SPECT) reported that individuals who were homozygous for e3 and e4 and individuals who were heterozygous for e4 had significantly higher values of a summed stress score (SSS) compared with those who were heterozygous for the e3 allele ( P  < 0.001) [22]. After adjustment for demographic and clinical risk factors, both APOE genotypes were independent predictors, with a cumulative contribution for the prediction of SSS and summed difference score.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…However, we believe that a better understanding of CAD development can be achieved through the analysis of genetic information combined with functional imaging. Although Izadpanah et al did not find any association between the rs2713604 polymorphism and premature MI, we have reported the independent correlations (after adjustment for various factors, including CAD risk factors) of several gene polymorphisms with myocardial ischemia, based on stressrest myocardial single-photon emission computed tomography (SPECT) imaging [4][5][6]. In particular, polymorphisms of the following genes were investigated: factor V Leiden, factor II prothrombin, plasminogen activator inhibitor 1, β-fibrinogen, factor XIII, apolipoprotein E, angiotensin l-converting enzyme, angiotensinogen, angiotensin II type 1 receptor, angiotensin II type 2 receptor, and renin.…”
mentioning
confidence: 56%
“…The ApoE4 gene was found to have the strongest association followed by ACED and Apog-219 T polymorphisms. [32] The combined structural and metabolic components secure a place in future of cardiovascular imaging; [116] this wealth of information, however, comes at the cost of higher levels of radiation (> 10 mSv), and lower availability. [93] The spatial resolution of PET is inherently low (4–8 mm), so that radiotracer activity in small coronary or even carotid arteries requires an additional imaging method, usually CT, to show the location of the abnormality.…”
Section: Petand Spectmentioning
confidence: 99%
“…Since CAD directed GWA studies began four years ago, many polymorphisms have been associated with hard endpoints of CAD, such as MI,[26,27] premature MI,[2832] and stroke (locus 4q25). [33] Sifting through the statistical noise, however, requires selecting effective phenotypic markers.…”
Section: Introductionmentioning
confidence: 99%